Answers

2016-07-09T23:07:20+08:00
X²-5x-6=0
you need to find 2 numbers when you add the answer is -5 and when you multiply the answer is -6..
this is my answer
(x-6)(x+1)using FOIL method you get the answer..
F=first term
O=outer
I=inner
L=last
(x.x)=x²(x.1)=1x
(-6.x)=-6x(-6.1)=-6
x²+1x-6x-6
=x²-5x-6
that is the answer☺



1 5 1
  • Brainly User
2016-07-10T00:03:58+08:00
Completing the square:

x² -5x + (5/2)² = 6 + (5/2)²

x² - 5x + (25/4) = 6 + 25/4

(x -  \frac{5}{2} )² = 49/4

 \sqrt{ (x+ \frac{5}{2}) ^{2} } =  \sqrt{ \frac{49}{4} }

x - 5/2 =  \frac{+}{-}  7/2

x₁ = +7/2 + 5/2               x₂ = -7/2 + 5/2
x₁ = 12/2                        x₂ = -2/2
x₁ = 6                             x₂ = -1
0